The impact of patient shadowing on service design: Insights from a family medicine clinic - Andrew Gallan; Bruce Perlow; Riddhi Shah; Judith Gravdal (The Beryl Institute, 2021)
A central tenet of patient-centered care is to truly and deeply understand how patients experience health care. One particular qualitative method, patient shadowing, holds the promise of seeing things through the patient's eyes in real time. The purpose of this research is to utilize patient shadowing to capture the realities of patient experiences in an outpatient family medicine clinic and to report opportunities for improvement to clinic leadership. A total of twenty (20) patients were shadowed at a family medicine outpatient clinic over the course of eight (8) different days, providing a variety of circumstances including staffing levels, shift changes, patient volume, and other factors. Patient shadowing revealed many interesting observations, capturing many best practices in delivering patient experiences as well as a short list of recommendations that could improve patients' and staff experiences. Areas for improvement include helping patients better understand the entire process, wayfinding from the exam room to check-out, and creating a checklist for patient follow-up items. Patient shadowing presents many benefits to health care organizations and employees, including enhanced communication and teamwork, a greater connection with patient experiences and hardships, and the opportunity to redesign processes to optimize efficiency and service quality. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens